Thermophysical characteristics and application of metallic-oxide based mono and hybrid nanocomposite phase change materials for thermal management systems. (25th November 2020) - Arshad, Adeel; Jabbal, Mark; Yan, Yuying
Abstract: This experimental study covers the chemical, physical, thermal characterization and application of novel nanocomposite phase change materials (NCPCMs) dispersed by TiO2, Al2 O3, and CuO nanoparticles for thermal management systems. A commercial-grade of paraffin, namely RT-35HC, was considered as a phase change material (PCM). The mono and hybrid NCPCMs were synthesized at a constant weight concentration of 1.0 wt. % . In the first phase, various characterization techniques were used to explore the thermophysical properties and chemical interaction of mono and hybrid NCPCMs. In the second phase, the thermal cooling performance was investigated by filling the prepared NCPCMs in a heat sink at various input power levels. The results showed the uniform dispersion of TiO2, Al2 O3, and CuO nanoparticles onto the surface of both mono and hybrid NCPCMs without altering the chemical structure of RT-35HC. The optimum latent-heat of fusion and highest thermal conductivity of 228.46 J/g and 0.328 W/m K were obtained, respectively, of Al2 O 3 + CuO dispersed hybrid NCPCM compared to pure RT-35HC. In comparison of RT-35HC, the increasing trend in specific heat capacity was observed of NCPCMs and 36.47% enhancement was obtained for hybrid NCPCM in solid-phase. The reduction in heat sink base temperature was achieved of 3.67%, 6.13%, 13.95% and 8.23% for NCPCM T i O 2, NCPCM A l 2 O 3, NCPCM C u O and NCPCM A l 2 O 3 + C u O, respectively, compared to RT-35HC. Further, no phase segregation, less subcooling, smaller phase transition temperature, higher chemical and thermal stability were observed with hybrid NCPCMs which can be used potentially for thermal management of electronic devices, Li-ion batteries and photovoltaic (PV) modules systems. Highlights: Synthesized the nanocomposite PCMs by dispersing TiO2, Al2 O3 and CuO nanoparticles. Characterized the physical, chemical, and thermal properties. Hybrid of Al2 O3 +CuO showed the 53.7% higher thermal conductivity enhancement. Improved thermal and chemical stability were observed in nanocomposite PCMs. Better cooling performance was observed with hybrid Al2 O3 +CuO nanocomposite PCM.